Physico-chemical, heavy metal, and microbiological analysis of effluent from a confectionery company in Lagos State, Nigeria (African Scientific Reports, 2025)
Wastewater from the confectionery industry exhibits marked daily and seasonal variations, complicating its management and disposal. This study investigated the physico-chemical characteristics, heavy metal content, and microbial load of effluents from a confectionery processing plant using American Public Health Association (APHA) standard procedures. At the discharge point, the effluent showed temperature (25.02±0.15 °C), turbidity (1.00 NTU), pH (6.20±0.29), electrical conductivity (2295.00±3.62 µs/cm), total dissolved solids (1708.00±19.70 mg/L), total suspended solids (6252.00±0.30 mg/L),  total hardness (CaCO3) (1141.30±0.03 mg/mL), oil and grease (5.60±0.00 mg/L±), dissolved oxygen (4.76±0.02 mg/L), COD (8900±0.00 mg/L), BOD (181.80±0.37 mg/L), free chlorine (0.25 mg/L), phosphate (9.418 mg/L), nitrate (387.60 mg/L). Heavy metals (mg/mL) included Mg (25.71), Zn (
Keywords: Effluent; Confectionery; Wastewater; Heavy metals; Coliform count